Green Accounting, Corporate Social Responsibility, dan Kinerja Lingkungan sebagai Determinan Kinerja Keuangan Perusahaan - Rapi Pajri; Hafizah Munawwaroh; Defid Fathur Rohman (Journal of Creative Student Research, 2025)
Modern companies face demands to integrate economic, social, and environmental aspects into business management to achieve long-term sustainability. Financial performance can no longer be separated from environmental and social responsibility practices. This article aims to examine the role of green accounting, Corporate Social Responsibility (CSR), and environmental performance as determinants of corporate financial performance. The research method used is a descriptive-conceptual approach through a systematic literature review of national and international journals relevant to the topic of corporate sustainability for the 2020-2025 period. The results of the study indicate that the implementation of green accounting enables companies to more accurately identify and control environmental costs, thereby improving operational efficiency and financial stability. CSR contributes to strengthening social legitimacy, corporate reputation, and investor and consumer trust, which positively impact long-term financial performance. Furthermore, good environmental performance has been shown to reduce regulatory and operational risks and increase the company’s attractiveness to ESG-based investors. The conclusion of this study confirms that the integration of green accounting, CSR, and environmental performance is a sustainable business strategy that conceptually supports the achievement of more stable and sustainable corporate financial performance.